PREVALENCE OF HEPATITIS C VIRUS ANTIBODIES IN RENAL TRANSPLANTED PATIENTS AND ITS IMPORTANCE - M.T. AKPOLAT; T. ARINSOY; N. ARIK; C. ÖZKUYUMCU; H. ŞİMŞEK; C. SUNGUR; Ü. YASAVUL; Ç. TURGAN; Ş. ÇAĞLAR; H. TELATAR (Turkish Journal of Gastroenterology, 2020)
-